2016
DOI: 10.1080/1359432x.2016.1176022
|View full text |Cite
|
Sign up to set email alerts
|

A constructively critical review of change and innovation-related concepts: towards conceptual and operational clarity

Abstract: The aim of this paper is to examine and clarify the nomological network of change and innovation (CI) -related constructs. A literature review in this field revealed a number of inter-related constructs that have emerged over the last decades. We examine several such constructs -innovation, creativity, proactive behaviours, job crafting, voice, taking charge, personal initiative, submitting suggestions, and extra-role behaviours. Our conceptual analysis suggests each one of these constructs represents a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 80 publications
(89 reference statements)
0
55
0
5
Order By: Relevance
“…Pre-implementation activities like idea selection play a crucial role in the innovation process (Potočnik & Anderson, 2016). For a long time, research on new product development has pointed to idea screening as one of the most challenging tasks for senior management (e.g., Baker & Albaum, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-implementation activities like idea selection play a crucial role in the innovation process (Potočnik & Anderson, 2016). For a long time, research on new product development has pointed to idea screening as one of the most challenging tasks for senior management (e.g., Baker & Albaum, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent meta-analytical evidence has showed that, despite being linked with previous well-established job performance dimensions of task, citizenship performance, and counterproductive behaviors (see Campbell & Wiernik, 2015;Rotundo & Sackett, 2002, for reviews), innovative performance is still empirically unique and distinct from them (Harari et al, 2016). Further research efforts focused on the nomological network of innovation-related have also contributed to clarify its behavioral scope as a performance criterion (Anderson et al, 2014;Potočnik & Anderson, 2016).…”
Section: Individual Innovation As a Key Performance Criterionmentioning
confidence: 99%
“…Drawing upon these developments, we conceptualize innovative performance as a multiphase behavioral process, including a set of intentional actions implied in the generation and implementation of new and useful ideas intended to improve the procedures, practices, or the products of the organization (Anderson et al, 2014). Hence, besides capturing the first phase of the innovation consisting of the development of new and beneficial ideas for the organization, which is commonly known as creativity, this criterion also encompasses the second phase of this process, which comprises the behaviors aimed at implementing these ideas into the workplace (Potočnik & Anderson, 2016;West & Farr, 1990). Notwithstanding, we further separate the second phase of the innovation process into idea promotion and idea implementation, following the approach of Kanter (1988), also adopted by Janssen (2000).…”
Section: Individual Innovation As a Key Performance Criterionmentioning
confidence: 99%
See 2 more Smart Citations